Oxidative Status Imbalance in Patients with Metabolic Syndrome: Role of the Myeloperoxidase/Hydrogen Peroxide Axis. (14th October 2014) - Fonseca, Lucas José Sá da; Nunes-Souza, Valéria; Guedes, Glaucevane da Silva; Schettino-Silva, Glauber; Mota-Gomes, Marco Antônio; Rabelo, Luíza Antas
Abstract : The present study evaluated the cardiometabolic and redox balance profiles in patients with Metabolic Syndrome compared to apparently healthy individuals, and the participation of the myeloperoxidase/hydrogen peroxide axis in systemic lipid peroxidation. Twenty-four patients with Metabolic Syndrome and eighteen controls underwent a full clinical assessment. Venous blood samples were collected for general biochemical dosages, as well as for the oxidative stress analyses (superoxide dismutase, catalase, and arginase activities; and lipid peroxidation, myeloperoxidase activity, nitrite, and hydrogen peroxide concentrations in plasma). Arterial stiffness was assessed by radial artery applanation tonometry. Plasma lipid peroxidation, erythrocyte superoxide dismutase activity, myeloperoxidase activity, and hydrogen peroxide concentrations were shown to be increased in Metabolic Syndrome patients, without significant differences for the other enzymes, plasma nitrite concentrations, and arterial stiffness. Linear regression analysis revealed a positive and significant correlation between lipid peroxidation and myeloperoxidase and also between this enzyme and hydrogen peroxide. In contrast, such correlation was not observed between lipid peroxidation and hydrogen peroxide. In summary, Metabolic Syndrome patients exhibited evident systemic redox imbalance compared to controls, with the possible participation of the myeloperoxidase/hydrogen peroxide axis as a contributor in lipid peroxidation.